20 years of transition in the agri-food sector - Gertrud Buchenrieder; Jon H. Hanf; Agata Pieniadz (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2009)
Prior to 1989 the world could be divided "economically" into three clusters: (1) The Eastern Bloc with its socialist, planned economies, (2) the Western Bloc with its more market-oriented systems, and (3) the developing and emerging countries. Then, at approximately the same time, some major political events took place which contributed to the collapse of the Eastern Block, for example the 1985 elections of the Soviet Parliament, which have been linked to the terms 'Perestroika', 'Glasnost', and 'Demokratisaziya'; the East German refugee camp in the German Embassy in Prague in September 1989; and last but not least the fall of the Berlin Wall. Thus came the beginning of the transition process from planned towards market economies in the former states of the Soviet Union (FSU) and Central and Eastern Europe (CEE). The challenges of transition were formidable. Private and public market-oriented institutions were absent and historical trading paths were interrupted. Many state-owned enterprises collapsed, the private sector was underdeveloped and the market organisations, as well as the producers and processors involved in the agri-food markets, did not know the rules of the "market" game. These issues led to deep and lasting economic distortions. Twenty years into the transformation of the agri-food sector in the approximately 30 countries that made up the former Eastern Bloc, it is time to recall the inherent changes that have occurred. Our introduction , but particularly the other contributions in this special issue on "20 years of transition in the agri-food sector - analyses of markets and policies" of the Agrarwirtschaft (vol. 58 with numbers 7 and 8), all serve as a platform to review the situation in the agri-food sector in light of the relatively heterogeneous country settings with regard to initial markets, policy and other institutions, as well as the subsequent driving forces of the transition process. 1. The 'communist' past and initial conditions. From a 'western' economic perspective, the agri-food sector of the former Eastern Bloc seemed organised in a coherent way. In reality, the Eastern Bloc countries had heterogeneous pre-reform characteristics. Countries differed in terms of the "length of time that the communist system [had] existed and the extent to which it was applied, in the distortions of the trade system and the forced integration with other communist countries, and in the level of economic development" (SWINNEN, 2007a: 19). Another differentiating feature "was the capital stock, the technology used in the farms, and the extent of the industrialisation of the agri-food chain" (ibid.). Thus, the initial conditions, including these systematic distortions, were quite heterogeneous. MACOURS and SWINNEN (2000) argue, however, that CEE countries, for instance Hungary, Czech Republic and Slovakia, were ranked at a lower level of initial distortions, while FSU countries such as Russia, Belarus and Ukraine encountered more severe distortions. Also with regard to the farming structure, tremendous differences existed. For instance, in the FSU or in Czechoslovakia, large farm structures (co-operatives or state-owned farms) dominated. Other countries such as Poland or Slovenia have been traditionally dominated by individual and rather small-scale farming. The differences in initial factor endowment and productivity, as well as the structure of the agri-food sector, in combination with political medium-term objectives, affected the choice of reforms. Today, the region presents itself in a very heterogeneous way with regard to structure and performance of the agri-food sectors. Overall, five important reform areas in the agri-food sector can be identified (CSAḰI, 2008). These are: (1) macro-economic and institutional reforms, particularly price liberalisation and subsidy cuts, (2) land privatisation and the reform of related organisations, (3) privatisation and modernisation of the agro-processing and food retail chain (value chain), (4) implementation of operational organisations related to the agri-food sector, and the (5) rural financial market. In the following, these reform areas are revisited and discussed. 2. Macroeconomic and institutional reforms The economic, legal and judicial, as well as political adjustment processes, as well as ongoing globalisation, have greatly impacted the agri-food sectors of the FSU and CEE. Already at the beginning of transition, fundamental reforms took place. First and foremost, the culture of setting production targets was dropped. Usually, the macro-economic reforms coincided with price liberalisation and cuts in both producer and consumer subsidies (HARTELL and SWINNEN, 1998). Additionally, reduced foreign demand after the collapse of the Council for Mutual Economic Assistance (CMEA) trading system, falling consumer incomes and a breakdown of the supply chains and state-owned enterprises, all caused major disruptions and thus a squeeze in investment and output (SWINNEN, 2007a). Furthermore, the breakdown of the industrial and, to some degree the agricultural state enterprises in rural regions, resulted in previously unknown high rural unemployment rates (on average 21%) that in many countries lasted until the late 1990s and longer (KOESTER, 1997; WORLD BANK, 2000). Currently, the agricultural sector and its marketing chain in the former Eastern Bloc are of much higher importance than in Western European countries. One-third of the approximately 500 million people in the former Eastern Bloc live in rural areas and many of them still depend on the agri-food sector for a living. Nevertheless, in line with overall positive economic development and general reform progress, the share of agriculture in gross domestic product (GDP), as well as those employed in agriculture is decreasing. Because the reforms were quite different regarding speed and depth, today huge differences exist among these countries. In this context, one can speak of four groups: (1) market economy in the "old" new member states, (2) advanced reformers, (3) moderate reformers, and (4) slow reformers (HEATH, 2003; CSAḰI et al., 2006; CSAḰI, 2008). In general, one can say that the effective implementation of legislation supporting private entrepreneurial activities, as well as privatisation and decentralisation, have caused a sharp increase of private business activities in all CEE countries. In addition, the prospect of EU accession has created an environment more conducive to reform efforts, foreign investments, and the inflow of technology and know-how. Particularly in those countries at the cusp of EU accession, this prospect drove reforms. This trend could be observed in all economic sectors, not just the agri-food sector (e.g. CSAḰI et al., 2000; LERMAN, 1998 and 1999). Nevertheless, the privatisation experience in the FSU and CEE suggests that a state's market-relevant institutions and organisations will tend to be unstable and corrupt so long as the competition for asset ownership remains unresolved among major interest groups. The theoretical and policy response, commonly referred to as the post-Washington Consensus , argued that the state needed to institute firm bases of market regulation and the rule of law prior to privatising entire economies. This institutional critique of markets paved the way for creating path-dependent reform programs tailored to specific countries. However, as the transition process did not allow for sufficient time to achieve this, transition seemed messier than normal politics and economics. Indeed, the sequencing and timing of reforms was often an issue of debate (transition in the FSU is often associated with a big bang while CEE opted more often for a gradual reform strategy). Eventually, institutions and organisations consistent with conventional economic fundamentals evolved once privatisation battles over assets were resolved (SCHWARTZ, 2006). 3. The impact of EU-policies on the transition progress. The possibility of EU membership accelerated reforms in the EU's acceding and candidate countries, since EU membership required these countries to fulfil the Copenhagen criteria, which includes the adoption of the acquis communautaire and its 2683 legal rules and regulations (COMMISSION OF THE EUROPEAN UNION, 2006a; CSAḰI, 2008).#Already two years after the accession of the ten new member states (NMS) , they had adopted 99% of the acquis - not always to the full satisfaction of the EU, but the possibility for changes and improvement was foreseen. The largest problems normally occurred in the legislation on competition (COMMISSION OF THE EUROPEAN UNION, 2006a). Recognising the specific needs of the NMS with regard to restructuring demands and the characteristic farm dualistic structure, the EU implemented financial support programs to support sustainable rural development. Prior to EU accession, the SAPARD program in particular focused on the agri-food sector and rural infrastructure, and under this program both the administrative agricultural service chain and its beneficiaries (farmers, processors) gained first-hand experience with measures similar to those provided under the Common Agricultural Policy (CAP). The majority of these funds were allocated to particular stages of the agri-food chain. For example, the support focused on investing in agricultural holdings and food processing (i.e., to facilitate the adoption of minimum [mandatory] quality standards), setting up producer groups (horizontal integration), or improving vocational training for actors in agri-business (knowledge transfer). However, it appears that mostly large units (farmers and processors) benefited from these measures due to their enhanced access to information and their possibilities to pre-finance and/or co-finance investment projects (COURT OF AUDITORS, 2004; LUCA, 2008). On the contrary, for most of the small and medium-sized units, a reduced capacity to co-finance investments (either through equity or debt-financing) was one of the main limiting factors that delayed the absorption of the SAPARD funds, especially in the first period of the program's implementation (COURT OF AUDITORS, 2004). For CEE farmers, EU membership was both a challenge and an opportunity. On the one hand, farms (operators in agri-food business) in countries which have already joined, or intend to join, the EU have been confronted with considerable changes in the economic and regulatory framework, as well as in market conditions. On the other hand, access to the single market and the various instruments of the CAP under Pillars 1 (direct payments and market support measures) and 2 (measures under the European Agricultural Fund for Rural Development) have opened new possibilities for farmers. The complementarities of the two CAP pillars were further strengthened with the CAP reform of 2003. Thus, one can state that the CAP reflects a policy shift that is called the New Rural Paradigm by the OECD (2006), and which places emphasis on regions rather than sectors, and investments rather than subsidies in rural development policy. In addition to the agri-rural development measures of the EU under Pillar 2, each member country is formulating a National Rural Development Program (NRDP). The NRDPs must be consistent with Community strategic guidelines, but they may indicate the nationally diversified priorities of action. For the NMS, additional transitional measures have been introduced in Pillar 2. These refer to the support of semi-subsistence agricultural holdings undergoing restructuring and the set-up of producer groups. Romania and Bulgaria, the newest member states, can potentially benefit from these measures until 2013. The objective of these measures is to improve the competitiveness of the agricultural sector by bringing small and semi-subsistence farms into the market (NRDP ROMANIA, 2008). In order to design a meaningful NRDP and to implement the policy measures effectively, the principle of decentralisation of responsibilities needs to be functioning, thus strengthening subsidiarity and partnership. For many NMS in CEE this is still a challenging task (MARQUARDT et al., 2009). Clearly, the introduction and strengthening of Pillar 2 was a well-received reform of the CAP. However, as for the NMS in CEE, the volume of the decoupled direct payments (notably the Single Payment Scheme which can be applied to area or farm units) under Pillar 1 are not only giving farmers a certain level of financial security but are also more substantial than the financial volume of measures under Pillar 2. Furthermore, the NMS can apply the simplified Single Area Payment Scheme (SAPS) until 2013 or in the case of Bulgaria and Romania even until 2016. Nevertheless, the rather complicated bureaucratic procedures required to obtain the payments under the SAPS are preventing this measure from reaching many smaller farm holders, who are in principle eligible. Here it appears that smaller-scale farms are rather disadvantaged due to their limited management capacity. Another interesting feature of the CAP is the so-called compulsory modulation (see footnote 7), that is, reducing spending on Pillar 1 measures and transferring the funds to be spent on Pillar 2 measures of the CAP. A certain percentage share of the direct payments to bigger farms (those receiving more than 5,000 exteuro of direct payments) is shifted to Pillar 2. Yet, this does not seem to make a significant difference for larger farms. What larger farms lose in Pillar 1, they may gain under Axis 1 "Improving the competitiveness of the agricultural and forestry sector" of Pillar 2 (CSAḰI, 2009; HAPPE et al., 2008; SAHRBACHER et al., 2008). Given the rather severe incidence of rural poverty and the lagging structural change in the farm sector of many CEE countries, including some of the NMS and the FSU, the question may be raised whether the CAP is sufficient to stimulate sustainable economic growth in the agri-food sector, respectively in the rural economy at large. A consensus is emerging that agri-rural policies alone cannot do the job. Farm exit options must be opened up, either in the sense of rural non-farm employment or via socially secure retirement (FELLMANN and MOL̈LERS, 2009). Adequate social safety networks have to be installed; bearing in mind that the state budgets of many transition countries are already stressed to their limits. This challenge calls for a more concerted effort in which the national and international political stakeholders of the agri-food sector, of the economy at large and of the social sector work closely together. 4. Land privatisation and reform of related organisations. The transformation of the agri-food sector was always prominent because one of the major reforms entailed the privatisation of land. The Commonwealth of Independent States (CIS) (and Albania) has adopted the 'land to tiller' strategy. This strategy implied that the land was allocated to workers of cooperatives without any payment in an equitable manner. In Russia, Ukraine and Kazakhstan, individuals received paper shares that certified their entitlement to a certain amount of land. Most CEE countries (except Albania) have chosen to restitute the land to former owners. All CEE countries, plus the small CIS countries (Armenia, Georgia, Moldova, and Azerbaijan) allocated physical plots to individuals (CSAḰI et al., 2000; NORTON, 2004). Often, an upper limit for land restitution was installed. The share system was intended to bring equitable land rights to the population, but it often brought about large-scale integrated farm structures and cooperatives (legal persons). Radical changes with regard to land tenure have been carried out in very few countries of the FSU. This is the case for Armenia, Georgia, and the Kyrgyz Republic, where independent private farming now dominates. In Uzbekistan and Tajikistan, private ownership of land is still prohibited by the constitution (CSAḰI, 2008). Where land was privatised, it was not so much driven by economic concerns, although theoretical considerations of land and labour productivity may have been considered. This privatisation process was rather prompted by a general sense of justice and had unintended effects in terms of land use changes and farm structures (SIKOR, 2009). Politics was willing to pay the economic price: an often-lamented dominance of small farm structures, a varied mix of small and large farm holdings, usually termed dualistic farm structure, or even land abandonment. Land consolidation is ongoing and is a critical issue for productivity gains.#The legal settlement of land ownership relations is also not yet complete, and the establishment of land registries and the emergence of a land market remain priority areas for further reform, especially in the FSU. 5. Reform of the rural financial market...6. Structure of agricultural production as an outcome of the transition process 7. Changes along the value chain 8. Conclusions References...
Keywords: 330; Agroindustrie; Agrarreform; Transformationsstaaten; GUS-Staaten; Osteuropa